2009
DOI: 10.1080/02640410802448749
|View full text |Cite
|
Sign up to set email alerts
|

Perfectionism and achievement goals in young Finnish ice-hockey players aspiring to make the Under-16 national team

Abstract: Research on perfectionism suggests that is it useful to differentiate between perfectionistic strivings and perfectionistic concerns. Regarding the 2 × 2 achievement goal framework, the usefulness of this differentiation was recently demonstrated in a study with university student athletes (Stoeber, Stoll, Pescheck, & Otto, 2008, Study 2) that found perfectionistic strivings associated with mastery-approach and performanceapproach goals and perfectionistic concerns with mastery-avoidance, performanceapproac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
59
1
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 61 publications
(63 citation statements)
references
References 41 publications
2
59
1
1
Order By: Relevance
“…As mentioned earlier, most people who show elevated levels of perfectionistic strivings also show elevated levels of perfectionistic concerns, as indicated by the significant (and often high) positive correlations between perfectionistic strivings and concerns found in terms of general perfectionism and perfectionism in sport (e.g., Stoeber, Otto, Pescheck, Becker, & Stoll, 2007;Stoeber, Stoll, et al, 2009). This represents a problem because perfectionistic concerns-while not necessarily leading to impaired performance-have shown close links with characteristics and processes that may impair performance.…”
Section: Implications For Applied Psychology [H1]mentioning
confidence: 84%
See 1 more Smart Citation
“…As mentioned earlier, most people who show elevated levels of perfectionistic strivings also show elevated levels of perfectionistic concerns, as indicated by the significant (and often high) positive correlations between perfectionistic strivings and concerns found in terms of general perfectionism and perfectionism in sport (e.g., Stoeber, Otto, Pescheck, Becker, & Stoll, 2007;Stoeber, Stoll, et al, 2009). This represents a problem because perfectionistic concerns-while not necessarily leading to impaired performance-have shown close links with characteristics and processes that may impair performance.…”
Section: Implications For Applied Psychology [H1]mentioning
confidence: 84%
“…The two dimensions-perfectionistic strivings and perfectionistic concerns-are best captured when each dimension is measured with multiple scales (Frost et al, 1993;; for a sport example, see Stoeber, Stoll, Salmi, & Tiikkaja, 2009). However, there are single scales that represent proxy measures of the two dimensions.…”
Section: Measures [H2]mentioning
confidence: 99%
“…To measure perfectionistic concerns, we also used two indicators: the 8-item SMPS subscale capturing concerns over mistakes ("People will probably think less of me if I make mistakes in competition") and the 5-item MIPS subscale capturing negative reactions to imperfection ( "I feel extremely stressed if everything does not go perfectly"), and again standardized the scale scores before combining them to measure perfectionistic concerns. The four subscales have demonstrated reliability and validity in previous studies (e.g., Madigan, Stoeber, & Passfield, in press;Stoeber, Stoll, et al, 2009) and are reliable and valid indicators of perfectionistic strivings and perfectionistic concerns (e.g., Gotwals et al, 2012;Stoeber & Madigan, 2016). Participants responded to all items on a scale from 1 (strongly disagree) to 5 (strongly agree).…”
Section: Methodsmentioning
confidence: 99%
“…Several studies have provided evidence that perfectionistic strivings and concerns show different relations with the 2 × 2 achievement goals in sports (e.g., Stoeber, Stoll, Salmi, & Tiikkaja, 2009;Stoeber, Uphill, & Hotham, 2009;Zarghmi, Ghamary, Shabani, & Varzaneh, 2010). Across studies, perfectionistic strivings have shown positive relations with masteryand performance-approach goals whereas perfectionistic concerns have shown positive relations with mastery-and performance-avoidance goals, suggesting that perfectionistic strivings are mainly approach-focused whereas perfectionistic concerns are mainly avoidancefocused (cf.…”
Section: Introductionmentioning
confidence: 99%
“…Según Stoeber y Otto (2006) es importante distinguir entre los esfuerzos y las preocupaciones perfeccionistas, debido a que estas últimas son principalmente las que marcan el perfeccionismo en el deporte. Contrariamente, los esfuerzos perfeccionistas son asociados con características positivas tanto en el proceso como en el resultado (Stoeber, 2011(Stoeber, , 2014Stoeber, Stoll, Salmi y Tiikkaja, 2009).…”
Section: Introductionunclassified